2015
DOI: 10.1016/j.diii.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic trauma and vascular emergencies

Abstract: Pelvic ring injuries carry a high mortality rate, the main cause of which, in the first 24hours, is exsanguination. Injured patients are managed by a multidisciplinary damage-control strategy. Unstable patients should have instrumentalized hemostasis without delay. Arterial embolization is an effective way of achieving this and justifies this approach being permanently available in level 1 trauma-centers. After CT assessment of injuries, stable patients can undergo arterial embolization if active arterial blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 58 publications
(62 reference statements)
1
22
0
Order By: Relevance
“…Most venous hemorrhages could be managed non-operatively. When arterial bleeding was combined with pelvic fracture, hemodynamic instability was frequent, and hemostasis was required [12]. Young et al [2] reported that a particular pelvic fracture pattern is associated with a major ligamentous disruption related to arterial bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most venous hemorrhages could be managed non-operatively. When arterial bleeding was combined with pelvic fracture, hemodynamic instability was frequent, and hemostasis was required [12]. Young et al [2] reported that a particular pelvic fracture pattern is associated with a major ligamentous disruption related to arterial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Such an event is diagnosed as blushing on CT or angiography. Scemama et al [12] reported that 75% of the cases of hemorrhage requiring angiography in the presence of contrast leakage were detected on CT scan. Angiography and embolization are effective in stopping arterial bleeding [8][9][10][11]17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…• subarachnoid hemorrhages and intracranial aneurysms [1][2][3]; • multiple injuries -damage to the aorta and its branches [4][5][6][7]; • gastrointestinal hemorrhage both from arterial causes and from portal hypertension [8,9]; • rupture of aneurysms of visceral branches of the aorta [10]; • the specific treatment of postoperative or postinterventional radiology and soft tissue oncology bleeding [11][12][13][14]; • hemoptysis and epistaxis [15,16].…”
Section: Vascular Emergencies: Diagnosis and Treatmentmentioning
confidence: 99%